Tree rings of Rhododendron arboreum portray signal of monsoon precipitation in the Himalayan region - Dhyani, Rupesh; Bhattacharyya, Amalava; Joshi, Rajesh; Shekhar, Mayank; Chandra Kuniyal, Jagdish; Singh Ranhotra, Parminder (Frontiers in Forests and Global Change, 2023)
The Himalayas has a significant impact not just on the Indian subcontinent’s monsoon patterns but also on the global climate. Monsoon failure causing drought has become more common in recent years. As a result, it poses a major threat to ecosystem sustainability. We reported for the first time, a climatic-sensitive tree ring chronology of a broadleaf tree, Rhododendron arboreum, spanning 1732–2017 CE from the Himalayan region. We discovered that the climate during the monsoon season limits the growth of this tree in this region. The correlation analysis between tree ring chronology and climate revealed a significant positive relationship with precipitation (r = 0.63, p < 0.001) and a negative relationship with temperature (r = −0.48, p < 0.01) during the months of June–August (JJA). This strong relationship allowed us to reconstruct monsoon precipitation spanning 1780 to 2017 CE which explained 40% of the variance of the observed climate data for the calibration period. The reconstructed data are validated by the existence of a significant association with the gridded JJA precipitation data of the Climate Research Unit (CRU) of this region. The monsoon rainfall record captured extremely wet years during 1793, 1950, 2011, 2013, and 2017 and extremely dry years during 1812, 1833, 1996, 2002, 2004, and 2005. The extremely dry and wet years well coincided with major catastrophic historical and instrumental droughts and floods in the region. Furthermore, the reconstructed data are also validated by the significant positive correlation (r = 0.36, p < 0.001, n = 163) with the all Indian summer monsoon rainfall series. Such data will be useful to predict the incidence of future droughts, which can help to assess the vulnerability of the forest ecosystem to extreme events.